Medya ve şiddet: mafya dizileri üzerine karma bir araştırma - (:unkn) unknown (My University, 2012)
Mafya dizileri, gerek içerdikleri aşırı şiddet görüntüleri, gerekse verdikleri açık ve örtülü mesajlarla yasa dışılığı ve sosyopatiyi özendirmekte, hatta meşrulaştırmaktadır. Bireylerin adalete karşı güven duyguları sarsılmaktadır. Mesajların tekrarlayan şekilde ve sürekli olarak kuvvetli biçimde verilmesi, gençlerin bu dizilerdeki karakterlere özenerek çevrelerine zarar verecek davranışlar geliştirmelerine neden olabilmektedir. Daha açık ifade edecek olursak; ergenler, mafya dizilerinden şiddeti öğrenmekte ve şiddete karşı duyarsızlaştırılmaktadırlar. Bu noktaları göz önünde bulunduran mevcut araştırmada, mafya dizilerinin toplumsal şiddet eğilimi üzerine etkileri incelenmiştir. Bu amaç çerçevesinde bazı bağımsız değişkenler açısından mafya dizilerinin toplum tarafından nasıl algılandığı irdelenmiştir. Araştırmada, katılımcıların mafya dizileri hakkındaki görüşlerini belirlemek amacıyla nicel ve nitel araştırma tekniklerinden faydalanılmıştır. Araştırmanın nicel kısmında katılımcıların mafya dizileri hakkındaki görüşlerinin belirlenmesi için Demografik Bilgiler Anketi ile Mafya Dizileri Tutum Ölçeğinden yararlanılmış; nitel kısmında ise katılımcıların konu hakkındaki düşüncelerini derinlemesine analiz edebilmek amacıyla olgubilim araştırma deseni kullanılmıştır. Buradaki amaç; araştırılan konuyu, ilgili bireylerin bakış açısından görebilmek ve bu bakış açılarını oluşturan sosyal yapıyı ve süreçleri ortaya koymaktır. Araştırmanın evrenini İstanbul ilinde görev yapmakta olan öğretmenler, avukatlar ve emniyet mensupları oluşturmaktadır. Bunlara ek olarak, yine aynı ilde öğrenim gören öğretmen adayları, hukukçu adayları ve lise öğrencileri örnekleme dahil edilmiştir. Araştırmada kullanılan Demografik Bilgiler Anketinden elde edilen sonuçlar, frekans ve yüzdelik tablolar halinde düzenlenerek yorumlanmıştır. Anketten yer alan bağımsız değişkenlere göre katılımcıların mafya dizileri hakkındaki tutum puanları arasındaki farklılık Bağımsız Grup t-Testi ve Tek Yönlü Varyans Analizi ile karşılaştırılmıştır. Tek Yönlü Varyans Analizinde istatistiksel açıdan fark oluşması durumunda, farkın kaynağını belirlemek amacıyla tamamlayıcı hesaplardan Scheffe ve Dunnett C testlerinden yararlanılmıştır. Araştırma kapsamında kullanılan tüm istatistiksel işlemlerde anlamlılık düzeyi 0.05 olarak kabul edilmiştir.

TV–serials portraying mafia organisations tempt and even legitimize illegal activities and sociopathy with not only violent scenes but also explicit and implicit messages they impose. The sense of trust against justice become disturbed. Imposing messages repeatedly, continuously and with increasing intensity cause young people emulating actors of those TV – serials and developing harmfull behaviors to their environment. More clearly; adolescents learn the violence in TV – serials and desensitized against the violence. In this research taking into account these points, the effect of TV – Serials portraying mafia organisations on the tendencies for social violence. In line with this goal, in terms of some independent variables, the perception of society on Mafia TV – serials was investigated. In the current study, qualitative and quantitative research methods was used in order to collect information about the views of the participants. In the quantitative part of the study, to collect information about the views of the participants on the Mafia TV – serials, “Demographical Information Survey” and “Mafia TV serials Attitute Scale” was used; in the qualitative part, in order to analyze the views of the participants on the topic at deep level, phenomological research design was used. The aim for using this design was to see the point of view of the participants and to understand what kind of social structures and processes form these point of views. The population of the study was composed of teachers, lavyers and, police officers working in Istanbul. In addition, candidates of being teacher, lavyer and high school students living in Istanbul participated to the study. The results obtained from “Demographical Information Form” was presented in the tables by using descriptive statisticts like percentages and frequencies. Based on the independent variables, the statistically significant differences of attitude scores against Mafia TV – serials among the participants was investigated by using Independent Groups T-test and One Way Analyses of Variance. In the cases of statistically signifigant differences when using One Way Analyses of Variance, further post hoc analyses was performed by using Scheffe and Dunnett C tests. The signifigance level of 0.05 was used for the interpretation of the analyses performed throughout the study. According to the findings, the attitudes of male partipants for Mafia TV – serials was found significantly higher that the attitudes of female participants. It is known that family, environment and media are the major factors contributing to violence. Media causes children to be receiver of thousands of violence scenes. There are many researchs about how the violence imposed by the media harm mental health of people and especially, effect violent attitutes and behaviors of children. In these researches, it was found that, children are affected by the media as they model significant figures imposed to them and are become unsensitized against violence. According to one another finding from the current study. Married participants had significanly higher attitude scores than the single ones. The children of families, migrating from small villages and try to adapt to urban life in Istanbul and to struggle with many kinds of problems, model the significant figures in Mafia TV-serials. Those young people fall into emulations and dreams and the imaginary figures in the serials turn into realities for the children. This situation causes to those uneducated children to exert violence unconsiously and unconrollably. As understood from the studies, mafia TVserials causes to society to become unsensitized toward violence. The fact that it media has great impact on the incerase in the learnt violence is an important proof for the effect of Media TV-serials on the youngs. Especially, increase in violent behaviors, insensitivity to violence, sleeping problems and nightmares and modeling of the aggressor was observed in children exposed to violent scenes and news. This finding supports what was found in the current study as well.
Media and violence: A mixed method study on mafia TV-serials
Keywords: Eğitim, Eğitim Araştırmaları